2018
DOI: 10.1002/jcb.27489
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mechanisms of crocetin‐induced differentiation and apoptosis in human acute promyelocytic leukemia cells

Abstract: Crocetin, the major carotenoid in saffron, exhibits potent anticancer effects. However, the antileukemic effects of crocetin are still unclear, especially in primary acute promyelocytic leukemia (APL) cells. In the current study, the potential antipromyelocytic leukemia activity of crocetin and the underlying molecular mechanisms were investigated. Crocetin (100 µM), like standard anti-APL drugs, all-trans retinoic acid (ATRA, 10 µM) and As O (arsenic trioxide, 50 µM), significantly inhibited proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…These results, which were in line with the microscopic considerations, suggested that attempted transitions from mesenchymal to neuronal lineage occurred in the GBM cells exposed to crocetin treatment. Different independent studies showed the capacity of crocetin to induce cancer cell differentiation through the inhibition of particular factors involved in the regulation of gene expression, such as HDACs [33,34]. Indeed, these proteins are important players in the onset and maintenance of tumors due to their inhibitory effects on the expression of suppressor genes in neoplastic disease.…”
Section: Discussionmentioning
confidence: 99%
“…These results, which were in line with the microscopic considerations, suggested that attempted transitions from mesenchymal to neuronal lineage occurred in the GBM cells exposed to crocetin treatment. Different independent studies showed the capacity of crocetin to induce cancer cell differentiation through the inhibition of particular factors involved in the regulation of gene expression, such as HDACs [33,34]. Indeed, these proteins are important players in the onset and maintenance of tumors due to their inhibitory effects on the expression of suppressor genes in neoplastic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate & Artemisinin , β-Elemene [138,139] Diterpenoids Triptolide [140][141][142][143][144][145][146][147][148][149][150][151][152][153][154], Crocetin [155][156][157][158][159][160][161][162][163][164][165], Phytol [166][167][168] Triterpenoids Ursolic acid [169][170][171][172][173][174][175][176][177][178][179][180], Betulinic acid [181][182][183][184][185][186][187]…”
Section: Classification Terpenoidsunclassified
“…Another study also reported that crocetin arrests KYSE-150 cells at the S phase, alters cell morphology and enhances the expression of Bax, and caspases apoptotic genes [158]. The anticancer molecular mechanism of crocetin in primary APL cells, HL60 cells and NB4 cells via the inhibition of pro-survival genes, such as Akt and Bcl-2, multidrug-resistant proteins (ABCB1 and ABCC1) and tyrosyl-DNA phosphodiesterase 1 (TDP1), as well as the overexpression of pro-apoptotic genes, such as caspase 3, 9 and Bax [159]. The tumor preventive effects of crocetin on N-methyl-N nitrosourea (NMU)-induced breast cancer in rats was also examined, where the inhibitory molecular mechanism triggered alterations in Bax and Bcl-2 expression levels, caspase activation, cell cycle arrest via cyclin D1, p21, and p53 modulation and interaction with DNA sequence [160].…”
Section: Crocetinmentioning
confidence: 99%
“…The lysates were examined for the protein expression of acetyl-H3K4, which was detailed in ref. (24).…”
Section: Western Blot Analysismentioning
confidence: 99%